Can we rely on magnetic resonance imaging when evaluating unstable atlantoaxial subluxation?. Issue 3 (1st March 2003) - Laiho, K; Soini, I; Kautiainen, H; Kauppi, M
Abstract : Objectives: To examine whether functional radiography and functional magnetic resonance imaging (MRI) are equally efficient in detecting the extent of unstable anterior atlantoaxial subluxation (aAAS) in rheumatic patients. Methods: 23 patients with unstable aAAS (diagnosed by functional radiography) were examined by functional MRI because of a neck symptom. Twenty two patients had rheumatoid arthritis and one had juvenile idiopathic arthritis. aAAS was diagnosed if the anterior atlantoaxial diameter (AAD) was >3 mm and was considered unstable if the AAD differed by >2 mm between flexion and extension radiographs. The AAD was measured from radiographs (flexion and extension) and MRI images (flexion and neutral). Results: The extent of aAAS during flexion measured by radiography was greater than that found by MRI in all 23 patients (mean difference 3 mm (95% confidence interval 2 to 4)). In four (17%) patients flexion MRI could not demonstrate aAAS detected by radiography. The difference between the AAD measurements during flexion by these two methods was substantial (that is, ⩾4 mm) in nine (39%) cases. Severe aAAS (⩾9 mm) was seen in 15 (65%) patients by functional radiography and in four (17%) by functional MRI. Conclusions: The magnitude of aAAS was often substantially smaller when measured by functional MRI rather than by functional radiography. Thus one cannot rely on the result of functional MRI alone; functional radiographs are needed to show the size of unstable aAAS. The maximal extent of the subluxation must be taken into account when the possible compression of neural structures is evaluated by MRI.